Hakikat Manusia dan Pendidikan : Perspektif Filosofis, Psikologis, dan Keislaman - Wina Eka Fauziah; Tika Mutiasari; Dini Indriani; Abdul Azis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Humans are not merely thinking beings but also emotional and spiritual creatures. However, modern education tends to prioritize the cognitive dimension and academic achievement, while psychological and spiritual aspects are often neglected. This imbalance has resulted in the emergence of intellectually capable generations who may lack emotional maturity and moral integrity. Therefore, an educational approach that incorporates philosophical, psychological, and Islamic values is essential in shaping a holistic human being. This study aims to analyze the nature of humans from a psychological perspective and its implications for designing holistic, learner-centered education. This research employs a qualitative approach using the library research method. Data collection was carried out through documentary studies by reading and reviewing written sources such as scientific books, journal articles, and other academic literature relevant to the research topic. The data were analyzed using content analysis, which includes identifying themes, categorizing key ideas, and drawing conceptual meanings from the collected data. The results show that from a psychological perspective, humans possess innate potentials that develop through specific stages, are influenced by environmental factors, and have a fundamental need for self-actualization. Humanistic, cognitive, and behaviorist psychological approaches all contribute to a more comprehensive understanding of human nature. The findings reinforce the notion that education focused solely on cognitive development is insufficient for shaping a well-rounded personality. Therefore, the education system must be oriented toward balanced development of the cognitive, affective, socialand spiritual dimensions of learners.